Basic Considerations for the Use of Monoclonal Antibodies in Migraine. Issue 10 (13th November 2018) - Levin, Morris; Silberstein, Stephen D.; Gilbert, Robert; Lucas, Sylvia; Munsie, Leanne; Garrelts, Alyssa; Kennedy, Kate; Everman, Nicole; Pearlman, Eric
Abstract : Background: Migraine impacts more than 36 million people in the United States and 1 billion people worldwide. Despite the increasing availability of acute and preventive therapies, there is still tremendous unmet need. Potential treatments in development include monoclonal antibodies (mAbs). Appropriate use of these "biologic" treatments will necessitate an understanding of the aspects that distinguish them from traditional medications. Aim: Many drug classes are prescribed for migraine treatment, but all have limitations. Recently, calcitonin gene‐related peptide (CGRP) activity has shown a significant promise as a target for preventive therapy. In this review, we provide an overview of the potential role of CGRP mAbs in migraine, with a focus on their design, pharmacokinetics, safety, and immunogenicity. Conclusions: The CGRP mAbs are an innovative new therapy for migraine and address the need for effective and tolerable preventive options. MAbs, including those that target CGRP or its receptor, bind to a target with high specificity and affinity and lead to few off‐target adverse effects, although mechanism‐based adverse reactions may occur. Unlike other therapeutic antibodies used to treat neurologic disease, CGRP mAbs do not have a target within the immune system and have been designed to avoid altering the immune system. The safety and efficacy of mAbs against CGRP or its receptors are being investigated in clinical development programs, and the first of these therapies has received regulatory approval in the United States.